Mathematical distribution of rainfall in arid and semi-arid zones of Rajasthan - KRISHNAN, A.; KUSHWAHA, R. S. (MAUSAM, 1972)
The mathematical distribution of accumulated rainfall for 2 pentads, 4 pentads….. 20 pentade commencing from the onset of monsoon has been studied in respect of a typical arid one station, viz., Jodhpur and semi-arid stations, namely, Jaipur in Rajasthan. In case of Jaipur, disribution beyond a month is normal while for Jodhpur, all accumulated pentads including the entire season is not normal at all. Probability charts using these theoretical distributions have been prepared and their utility discussed.